A Study of Serum Zinc, Iron, Selenium, and Copper levels in patients with bladder cancer - Dawood, Sura Dhafir; Zainab Fadthel Ashoor (Iraqi Journal of Cancer and Medical Genetics, 2010)
Back ground: The association of serum trace elements like Zinc, Iron, Selenium, and copper has been found in different types of cancer. Many authors observed direct association between micronutrient deficiency and the cancer mortalities. Many of essential trace element are required for growth “ play an important role in the suitable biochemistry of the body “ and they could also stimulate the growth of tumors. Objectives : Assessment the level of trace element ( Zn, Fe, Se, and Cu ) in serum of patients with bladder cancer. Patients & Methods: Serum samples of (40) male and female patients with bladder cancer and (20) healthy controls were enrolled in this study. Bladder cancer patients were undergo cystoscopy and diagnosed clinically by consultant urologist as newly diagnosed for primary bladder tumor. Tumor characterized by 2 independent pathologists according to the criteria of WHO . Trace element were determined by Automic Absorption Spectrophotometer. Results : Significant increase in serum (Cu) levels and significant decrease in serum (Zn, Fe, and Se) levels in bladder cancer patients when compared with normal group. Conclusion : Low serum ( Zn, Fe, and Se) and high Cu levels in bladder cancer patients when compared with control indicates the role of bladder cancer disorders in trace elements metabolism. Key words: Trace elements, bladder cancer.